Development of an Asian Carp Size Structure Index and Application through Demonstration. (6th March 2013) - Phelps, Quinton E.; Willis, David W.
Abstract: Asian carp (Cyprinidae) are among the most invasive fishes in North America, but assessment tools for evaluating stock structure have not been established. Thus, we used data from national and international published reports or manuscripts to develop standard length categories for four species of Asian carp. Due to the similarities in maximum reported size for Bighead Carp Hypophthalmichthys nobilis and Grass Carp Ctenopharyngodon idella, we propose the following standardized length categories for those two species: stock = 30 cm, quality = 54 cm, preferred = 68 cm, memorable = 89 cm, and trophy = 111 cm. Proposed Black Carp Mylopharyngodon piceus length categories are stock = 40 cm, quality = 72 cm, preferred = 90 cm, memorable = 118 cm, and trophy = 148 cm. Finally, we propose the following length categories for Silver Carp H. molitrix : stock = 25 cm, quality = 45 cm, preferred = 56 cm, memorable = 74 cm, and trophy = 93 cm. We then used existing data collected in the Illinois River and Mississippi River from 2003 to 2011 to evaluate Silver Carp proportional size distribution (PSD). Incremental PSD provided a temporal index of Silver Carp size structure in the Illinois River and strong cohorts could be followed through the incremental PSD values over time. Traditional PSD provided a quantifiable, comparative index of Silver Carp size structure among two locations in the Mississippi River and one location in the Illinois River. We believe this index provides an additional tool for fisheries managers to evaluate size structure of Asian carp and help assess overall population status. Received September 19, 2012; accepted December 12, 2012